EFFECT OF ECONOMIC FREEDOM ON CARBON DISCLOSURE: AN INTERNATIONAL INVESTIGATION - Pinheiro, Alan Bandeira; de Melo de Albuquerque Ribeiro, Cintia; Mazzioni, Sady; Batistella, Ana Júlia (Advances in Scientific and Applied Accounting, 2022)
Objective: This study investigates how the institutional variables of economic freedom affect the disclosure of carbon by companies. Method: Data from a sample of 1,328 companies based in the 19 countries that emit the most carbon into the atmosphere is analyzed through a hierarchical regression, in which the dependent variable is the disclosure of carbon, and the independent variables represent the degree of economic freedom of the countries. Results: The results found indicate that companies disclose more information about carbon emissions in countries with greater government participation in the economy and where the law is more enforced. Contribution: Our study brings new evidence about the determinants of carbon disclosure using the theoretical lens of the Varieties of Capitalism (VoC) approach, in addition to important contributions for policy makers and managers. Keywords: Economic Freedom; Carbon Disclosure; Corporate Social Responsibility; Varieties of Capitalism.